2019
DOI: 10.1002/acn3.50923
|View full text |Cite
|
Sign up to set email alerts
|

PAI‐1 5G/5G genotype is an independent risk of intracranial hemorrhage in post‐lysis stroke patients

Abstract: Objective: Thrombolysis by recombinant tissue plasminogen activator (rt-PA) is the main pharmacological therapy in acute ischemic stroke (IS); however, it is only effective in a subset of patients. Here we aimed to investigate the role of plasminogen activator inhibitor-1 (PAI-1), an effective inhibitor of t-PA, and its major polymorphism (PAI-1 4G/5G) in therapy outcome. Methods: Study population included 131 consecutive IS patients who all underwent thrombolysis. Blood samples were taken on admission, 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Interestingly, here we show that with the exception of plasminogen levels at admission, there is no direct relation between thrombus size and the investigated fibrinolysis parameters at admission or 24 h later. In a previous study by our group involving 131 AIS patients, we found that PAI-activity and antigen levels before thrombolysis, 1 hour and 24 hours after thrombolysis showed no association with short‐term or long‐term functional outcomes [ 29 ], thus levels of this marker were not measured in this cohort. In this patient cohort, plasminogen levels were significantly lower in case of higher CBS (smaller thrombi) that might be a result of significantly higher incorporation of plasminogen to thrombi and as a consequence, the consumption of the protein.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, here we show that with the exception of plasminogen levels at admission, there is no direct relation between thrombus size and the investigated fibrinolysis parameters at admission or 24 h later. In a previous study by our group involving 131 AIS patients, we found that PAI-activity and antigen levels before thrombolysis, 1 hour and 24 hours after thrombolysis showed no association with short‐term or long‐term functional outcomes [ 29 ], thus levels of this marker were not measured in this cohort. In this patient cohort, plasminogen levels were significantly lower in case of higher CBS (smaller thrombi) that might be a result of significantly higher incorporation of plasminogen to thrombi and as a consequence, the consumption of the protein.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, in approximately 6-8% of patients, therapy-associated bleeding complications will take place, which potentially leads to worsening of symptoms and might be fatal in approximately 1% of thrombolysed patients [6]. The outcome and safety of thrombolysis is likely to depend on factors influencing or regulating fibrinolysis, but the exact pathomechanism is largely unknown [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, another study showed that the PAI-1 5G/5G genotype is associated with an increased risk of hemorrhage after rt-PA treatment. Furthermore, PAI-1 levels were increased significantly in patients who had ASPECTS scores below 7 points [39].…”
Section: Discussionmentioning
confidence: 92%